Laparoscopic left lateral sectionectomy: a population-based study. Issue 2 (February 2017) - Goutte, Nathalie; Bendersky, Noelle; Barbier, Louise; Falissard, Bruno; Farges, Olivier
Abstract: Background: Laparoscopic left lateral sectionectomy (LLS) has now become standard practice. However, published series are small and retrospective. The aim was to compare at a national level the use and short-term outcome of laparoscopic and open LLS. Methods: National hospital discharge databases were screened to identify all adult patients who had undergone elective LLS in France between 2007 and 2012. Outcome measurements included blood transfusion, severe morbidity, mortality and length of hospital stay. The independent influence of the laparoscopic approach on these outcomes was tested overall and after stratifying for the indication (benign condition, primary malignancy, liver metastasis). Results: Over the 6-year study period, 2198 patients underwent LLS, accounting for 6.9% of all elective liver resections. Some 28.5% of LLS procedures were performed laparoscopically. Among hospitals in which LLS was carried out, 33.2% of procedures were done laparoscopically (median 2 laparoscopic LLS resections per year). The laparoscopic approach was independently associated with a shorter length of hospital stay irrespective of the indication, and a lower transfusion rate in patients with benign condition or primary malignancy. Conclusion: LLS is seldom performed and the laparoscopic approach has not been adopted widely. The potential benefit of laparoscopic LLS varies according to the indication.